Writing Sprints untuk Publikasi Ilmiah Mahasiswa pada Pembelajaran Berbasis Capaian: Sebuah Penelitian Tindakan Kelas - Cermi City Mulyanti; Wahyudin Darmalaksana (Journal of Society and Development, 2021)
The strategy for the success of scientific publications for students is very much needed in learning achievement-based subjects. This study aims to analyze the application of Writing Sprints in article writing among students for the effectiveness of publication in scientific journals. This study applies a qualitative approach using descriptive-analytical method. The results of the research and discussion show that Writing Sprints has produced two student scientific publications in two weeks supported by modules, reviews, and feedback factors. This is a finding that the student's lecture period can be taken in a short time in a course with achievement-based learning, depending on the strategy applied. The conclusion of this study is that the module, review, and feedback factors are very decisive in learning based on the achievement of scientific publications through the Writing Sprints approach.